Determining the Minimum Time Interval for Completely Eliminating the Carryover Effect of Dehydration in Heat-Stressed Goats: Insights from Physiochemical Mechanisms - Samara, E. M.; Al-Badwi, M. A.; Abdoun, K. A.; Al-Haidary, A. A. (Tropical Animal Science Journal, 2024)
Heat stress, coupled with water deprivation, is widely acknowledged as one of the most potent stressors capable of impairing the production performance of small ruminants; therefore, comprehending and mitigating this stressor is of paramount importance. This experiment aimed to investigate the physiochemical adaptability of heat-stressed goats to periods of water deprivation and subsequent rehydration, focusing on determining the minimum time interval required to fully eliminate the carryover effects. Nine healthy Aardi bucks, aged 10 months and weighing 29.14±1.06 kg, underwent three experimental stages: euhydration (EU), dehydration (DE), and rehydration (RE). The EU and DE stages lasted 72 hours each, while the RE stage extended to 10 days. Physiochemical responses, including daily feed intake (DFI), rectal temperature (RT), respiratory rate (RR), hematology, biochemistry, and hemogasometry, were all monitored. Exposure of heat-stressed goats (as evidenced herein by the temperature-humidity index values) to complete water deprivation during the DE stage had manifested significant modulation in their physiological responses (DFI, RT, and RR), which thereby led to notable changes in their hematological, biochemical, and hemogasometric profiles. Surprisingly, blood pH remained unchanged throughout the experiment, underscoring goats’ remarkable adaptive mechanisms to tolerate infrequent liquid intake in their natural hot and arid environment. Notably, all measured variables completely returned to EU levels after 10 days of commencing the RE stage. Based on the obtained findings, a minimum recovery period of 10 days post-rehydration is recommended to eliminate carryover impacts of water deprivation for 72 hours before conducting any further experiments on heat-stressed and water-deprived goats. This research contributes to enhancing goat welfare under harsh environmental conditions.